Post-anthesis dry matter and nitrogen accumulation, partitioning, and translocation in maize under different nitrate–ammonium ratios in Northwestern China - Wu, Bing; Cui, Zhengjun; Zechariah, Effah; Guo, Lizhuo; Gao, Yuhong; Yan, Bin; Liu, Hongsheng; Wang, Yifan; Wang, Haidi; Li, Li (Frontiers in Plant Science, 2024)
Introduction An appropriate supply of ammonium (NH4+) in addition to nitrate (NO3−) can greatly improve plant growth and promote maize productivity. However, knowledge gaps exist regarding the mechanisms by which different nitrogen (N) fertilizer sources affect the enzymatic activity of nitrogen metabolism and non-structural carbohydrates during the post-anthesis period. Methods A field experiment across 3-year was carried out to explore the effects of four nitrateammonium ratio (NO3−/NH4+ = 1:0 (N1), 1:1 (N2), 1:3 (N3), and 3:1 (N4)) on postanthesis dry matter (DM) and N accumulation, partitioning, transportation, and grain yield in maize. Results NO3-/NH4+ ratio with 3:1 improved the enzymatic activity of N metabolism and non-structural carbohydrate accumulation, which strongly promoted the transfer of DM and N in vegetative organs to reproductive organs and improved the pre-anthesis DM and nitrogen translocation efficiency. The enzymatic activities of nitrate reductase, nitrite reductase, glutamine synthetase, glutamine oxoglutarate aminotransferase, and non-structural carbohydrate accumulation under N4 treatment were increased by 9.30%–32.82%, 13.19%–37.94%, 4.11%–16.00%, 11.19%–30.82%, and 14.89%–31.71% compared with the other treatments. Mixed NO3−-N and NH4+-N increased the total DM accumulation at the anthesis and maturity stages, simultaneously decreasing the DM partitioning of stem, increasing total DM, DM translocation efficiency (DMtE), and contribution of pre-anthesis assimilates to the grain (CAPG) in 2015 and 2017, promoting the transfer of DM from stem to grain. Furthermore, the grain yield increased by 3.31%–9.94% (2015), 68.6%–26.30% (2016), and 8.292%–36.08% (2017) under the N4 treatment compared to the N1, N2, and N3 treatments. Conclusion The study showed that a NO3−/NH4+ ratio of 3:1 is recommended for high-yield and sustainable maize management strategies in Northwestern China.